Artificial Pollination and Fruit formation in Black Mulberries (Morus nigra L.) - Mehmet Akif Demirel; Kenan Yıldız (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this study was to investigate the pollination and fertilization biology of black mulberry (Morus nigra L.), with a specific focus on understanding the effects of different pollination treatments on fruit formation and seed formation. Two experiments were designed to evaluate both dioecious and monoecious genotypes. In the first experiment, genotype 25 (dioecious female) was subjected to various artificial pollination treatments using pollen from two male genotypes (genotype 5 and genotype 28), as well as isolation treatments to observe parthenocarpic fruit formation. High fruit formation rates were recorded across all treatments, and no significant differences in fruit size or drupelet number were observed, regardless of the pollen source. The second experiment involved three monoecious genotypes (genotype 1, genotype 30, and genotype 31), where significant variations in fruit formation and size were observed, depending on the pollen source. This study highlights the potential for both fertilized and parthenocarpic fruit formation in black mulberry and underscores the importance of pollen source in determining fruit quality and seed formation.